Racial differences in venous thromboembolism: A surveillance program in Durham County, North Carolina. Issue 5 (21st July 2022) - Saber, Ibrahim; Adamski, Alys; Kuchibhatla, Maragatha; Abe, Karon; Beckman, Michele; Reyes, Nimia; Schulteis, Ryan; Pendurthi Singh, Bhavana; Sitlinger, Andrea; Thames, Elizabeth H.; Ortel, Thomas L.
Abstract: Background: Venous thromboembolism (VTE) affects approximately 1–2 individuals per 1000 annually and is associated with an increased risk for pulmonary hypertension, postthrombotic syndrome, and recurrent VTE. Objective: To determine risk factors, incidence, treatments, and outcomes of VTE through a 2‐year surveillance program initiated in Durham County, North Carolina (population approximately 280, 000 at time of study). Patients/Methods: We performed a retrospective analysis of data actively collected from three hospitals in Durham County during the surveillance period. Results: A total of 987 patients were diagnosed with VTE, for an annual rate of 1.76 per 1000 individuals. Hospital‐associated VTE occurred in 167 hospitalized patients (16.9%) and 271 outpatients who were hospitalized within 90 days of diagnosis (27.5%). Annual incidence was 1.98 per 1000 Black individuals compared to 1.25 per 1000 White individuals ( p  < 0.0001), and Black individuals with VTE were younger than White individuals ( p  < 0.0001). Common risk factors included active cancer, prolonged immobility, and obesity, and approximately half were still taking anticoagulant therapy 1 year later. A total of 224 patients died by 1 year (28.5% of patients for whom outcomes could be confirmed), and Black patients were more likely to have recurrent VTE than White patients during the first 6 months following initial presentation (9.4% vs. 4.1%, p  = 0.01). Conclusions: Ongoing surveillance provides an effective strategy to identify patients with VTE and monitor treatment and outcomes. We demonstrated that hospital‐associated VTE continues to be a major contributor to the burden of VTE and confirmed the higher incidence of VTE in Black compared to White individuals.